Terapia cognitivo-comportamental para casais em conflitos: estudo de caso - Nascimento, Fabiana Souto Pocol (2016)
A significant number of couples has been suffering due to their conflicting relations, with the increase in search for Psychology services. Objective: to describe the use of cognitive-behavioral therapy as treatment for couples in conflict. Method: this research is a qualitative case study. For the recruitment of the participants posters were fixed in clinics and private practices. Four couples have expressed interest, fit the criteria of inclusion and initiated the procedure, one of these reached the end becoming the object of study. A protocol was used, containing identification sheet, socio-demographic conditions, semi-structured interviews and a questionnaire developed by researchers from the relevant literature. In accordance with the requirements established in the initial data, participants received cognitive-behavioral interventions for seventeen meetings with duration of 1 hour and a half each. Socratic questioning techniques were used for cognitive restructuring, training of communication skills, problem solving, empathy, stress and time management for promotion of performances. At the end, they were evaluated with the same instruments and procedures used initially. The data were transcribed and subsequently analyzed qualitatively, by grouping with similar semantics. Results: an initial assessment, the spouses have submitted complaints of fights and frequent discussions, no knowledge of how to handle disagreements and conflict, inappropriate dialogue, lack of patience, nervousness, irritability, rudeness and insults. After intervention, the spouses showed improvements in levels of marital satisfaction, empathy, increase care and appropriate strategies for conflict resolution and communication. Final Remarks: the techniques and the intervention model employed demonstrated effectiveness in the treatment of the couple. Studies of this population are reduced, so the search will allow you to add relevant information to the subject.